Economic Growth And Carbon Emissions In Asean-6 To Achieve Sustainable Development Goals Through Kuznet Curve Environmental Analysis Approach - Soeharjoto, Soeharjoto; Salma, Nabila Inas; Tribudhi, Debbie Aryani; Masyhudi, Lalu (Politeknik APP Jakarta, 2022)
This study aims to determine carbon emissions in the Association of Southeast Asian Nations-6 (ASEAN-6) in achieving Sustainable Development Goals using the Kuznet environmental curve analysis approach. Used panel data regression method with carbon emissions as a dependent variable and Gross Domestic Product per capita, Squared Gross Domestic Product per capita, population, energy consumption and Sustainable Development Goals as independent variables. Used panel data from 2009-2018, samples taken from Singapore, Malaysia, Indonesia, Thailand, Philippines and Vietnam. Results are the suitable random effect model, with per capita Gross Domestic Product and energy consumption having a positive and significant effect on carbon emissions. In contrast, the squared Gross Domestic Product Per capita, population and Sustainable Development Goals have a negative and significant impact on carbon emissions. The Environmental Kuznet curve hypothesis has been proven in this area, although only Singapore has reached a turning point, so ASEAN-6 will still experience in carbon emissions increase. For this reason, ASEAN-6 needs to implement sustainable development policies, family planning, environmentally friendly energy development, and coordination and seriousness in implementing the Sustainable Development Goals.